BIPLOT ANALYSIS ON PRINCIPAL COMPONENTS OF HUMAN DEVELOPMENT IN ASEAN COUNTRIES - Deva A. Nurul Huda; Pardomuan Robinson Sihombing (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2021)
The Human Development Index (HDI) has been the key indicator for assessing the development of a country throughout the years. It is conducted from four indicators that represent the health dimension, the education dimension, and the standard of living dimension. In ASEAN countries, the HDI tends to rise from year to year, with some countries can achieve the very high and high level of human development, while the others are still in the medium level. The aim of this study is to find the information about relative positions, characteristic similarities between ASEAN countries and the diversity of the components that construct the human development index. The Principal Component Analysis Biplot used divides the ten countries into four groups. Group 1 are the countries with the high scores especially in GNI per capita, group 2 are the ones with high scores especially in the mean years of schooling, group 3 have low scores especially in GNI per capita, and group 4 have low scores especially in the mean years of schooling